Exergames como recursos de tecnologia assistiva a estudantes com paralisia cerebral: análise do desempenho e das adaptações de estratégias de ensino - Santos, Elaine De Oliveira [UNESP]; Seabra, Manoel Osmar [UNESP]; Araujo, Monique Yndawe Castanho [UNESP] (Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira, 2024)
Exergames are part of a category of digital games that use movement as a form of interaction between the user and the game. Due to motor alterations, users affected by cerebral palsy (CP), in particular, have difficulties in interacting with these games. The objective of this study was to analyze the performance of students with CP and the teaching strategy adaptations in interventions with exergames. Six students diagnosed with CP participated in the study. Intervention sessions totaled 75 records. Performance was analyzed using an observation script with five analysis items: independence, attention/concentration, range of motion, reaction time, and frequency of support, associated with a correlation between the variables ‘number of sessions’ versus ‘the score’. Adaptations were analyzed using field notes, filming, and data triangulation. It was concluded that the exergames skiing, tennis, and boxing can be considered as assistive technology resources, since the students were able to participate in the activities in a functional way and performed the tasks/actions with greater independence and less support. The adaptations enabled access to different sports modalities. With these adaptations, Kinect can capture movements, carry out/select the initial settings, and make the game viable in a sitting position, such as in a wheelchair, consequently, facilitating autonomy in the game as a whole.

Los exergames hacen parte de una categoría de juegos digitales que utilizan el movimiento como forma de interacción entre el usuario y el juego. Los usuarios, especialmente los afectados por parálisis cerebral, tienen dificultades para interactuar con estos juegos, debido a alteraciones motoras. El objetivo de este estudio fue analizar el desempeño de estudiantes con parálisis cerebral y las adaptaciones de estrategias de enseñanza en intervenciones con exergames. En el estudio participaron seis estudiantes diagnosticados con parálisis cerebral. Las sesiones de intervención totalizaron 75 registros. El desempeño se analizó mediante un guion de observación con cinco ítems de análisis: independencia, atención/concentración, amplitud de movimiento, tiempo de reacción y frecuencia de apoyo, asociado a una correlación entre las variables “número de sesiones” y “puntajes”. Las adaptaciones fueron averiguadas mediante notas de campo, filmaciones y triangulación de datos. Se concluyó que los exergames de esquí, cancha de tenis y boxeo pueden ser considerados como recursos de tecnología de asistencia, ya que los estudiantes pudieran participar en las actividades de manera funcional y realizaron las tareas/acciones con mayor independencia y menor apoyo. Las adaptaciones permitieron el acceso a diferentes deportes. Con estas adaptaciones, Kinect puede capturar movimientos, realizar/seleccionar configuraciones iniciales y permitir el juego en una posición sentada, como en una silla de ruedas, promoviendo, consecuentemente, autonomía en el juego en su conjunto.

Os exergames fazem parte de uma categoria de jogos digitais que utiliza o movimento como forma de interação entre o usuário e o jogo. Os usuários, em especial quando acometidos por paralisia cerebral (PC), apresentam dificuldades na interação com esses jogos, em virtude das alterações motoras. O objetivo deste estudo foi analisar o desempenho de estudantes com PC e as adaptações de estratégias de ensino em intervenções com exergames. Participaram do estudo seis estudantes diagnosticados com PC. As sessões de intervenções totalizaram 75 registros. O desempenho foi analisado mediante um roteiro de observação com cinco itens de análise: independência, atenção/concentração, amplitude de movimento, tempo de reação e frequência de apoio, associados a uma correlação entre as variáveis “número de sessões” e “pontuação”. As adaptações foram analisadas por meio de notas de campo, filmagem e por triangulação de dados. Concluiu-se que os exergames esqui, tênis de quadra e boxe podem ser considerados como recursos de tecnologia assistiva, uma vez que os estudantes conseguiram participar das atividades de forma funcional e executaram as tarefas/ações com maior independência e menor apoio. As adaptações possibilitaram o acesso às diferentes modalidades esportivas. Com essas adaptações, o Kinect pode captar movimentos, realizar/selecionar as configurações iniciais e viabilizar o jogo na posição sentada, como na cadeira de rodas, consequentemente, promover autonomia no jogo como um todo.
Exergames as an assistive technology resource for students with cerebral palsy: analysis of performance and teaching strategy adaptations
Exergames como recursos de tecnología de asistencia para estudiantes con parálisis cerebral: análisis del desempeño y adaptaciones de estrategias de enseñanza
Keywords: special education; assistive technology; exergames; cerebral palsy; games; educação especial; tecnologia assistiva; exergames; paralisia cerebral; jogos